Surfactant–soil interactions during surfactant-amended remediation of contaminated soils by hydrophobic organic compounds: A review - Laha, Shonali; Tansel, Berrin; Ussawarujikulchai, Achara (Journal of environmental management, 2009)
Surfactants are amphiphilic molecules that reduce aqueous surface tension and increase the solubility of hydrophobic organic compounds (HOCs). Surfactant-amended remediation of HOC-contaminated soils and aquifers has received significant attention as an effective treatment strategy – similar in concept to using soaps and detergents as washing agents to remove grease from soiled fabrics. The proposed mechanisms involved in surfactant-amended remediation include: lowering of interfacial tension, surfactant solubilization of HOCs, and the phase transfer of HOC from soil-sorbed to pseudo-aqueous phase. However, as with any proposed chemical countermeasures, there is a concern regarding the fate of the added surfactant. This review summarizes the current state of knowledge regarding nonionic micelle-forming surfactant sorption onto soil, and serves as an introduction to research on that topic. Surfactant sorption onto soil appears to increase with increasing surfactant concentration until the onset of micellization. Sorbed-phase surfactant may account for the majority of added surfactant in surfactant-amended remediation applications, and this may result in increased HOC partitioning onto soil until HOC solubilization by micellar phase surfactant successfully competes with increased HOC sorption on surfactant-modified soil. This review provides discussion of equilibrium partitioning theory to account for the distribution of HOCs between soil, aqueous phase, sorbed surfactant, and micellar surfactant phases, as well as recently developed models for surfactant sorption onto soil. HOC partitioning is characterized by apparent soil–water distribution coefficients in the presence of surfactant.